2021
DOI: 10.1037/cou0000495
|View full text |Cite
|
Sign up to set email alerts
|

Group as a social microcosm: The reciprocal relationship between intersession intimate behaviors and in-session intimate behaviors.

Abstract: The social microcosm is defined as group members replicating their everyday (intersession) interpersonal behaviors in group sessions and new behaviors, learned in the group (in-session), replicating in the members' everyday life. We examined intersession and in-session intimate behaviors, at the withinmember (differences in intimate behaviors between weeks/sessions), between-member (average differences in intimate behaviors between group members) and between-groups (group-level differences in intimate behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Research (D. M. Jr. Kivlighan, et al, 2020) provides support for the social microcosm theory where clients bring their psychosocial qualities (e.g., gratitude, psychological need satisfaction, positive affect, good relationships with others, or perceived social support) to interactions with others in a group counseling session and skills learned in the group are taken to relationships outside of the group (e.g., Yalom & Leszcz, 2005). Having positive emotions (e.g., gratitude) and positive relations (e.g., a teacher-student relationship or perceived social support) could allow children and adolescents to expand their vision and broaden their thoughts and actions to have more ideas for different interpretations in a given situation and more strategies to solve problems (Fredrickson & Branigan, 2005), which could be helpful to cultivate emotion regulation.…”
Section: Positive Emotions and Positive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research (D. M. Jr. Kivlighan, et al, 2020) provides support for the social microcosm theory where clients bring their psychosocial qualities (e.g., gratitude, psychological need satisfaction, positive affect, good relationships with others, or perceived social support) to interactions with others in a group counseling session and skills learned in the group are taken to relationships outside of the group (e.g., Yalom & Leszcz, 2005). Having positive emotions (e.g., gratitude) and positive relations (e.g., a teacher-student relationship or perceived social support) could allow children and adolescents to expand their vision and broaden their thoughts and actions to have more ideas for different interpretations in a given situation and more strategies to solve problems (Fredrickson & Branigan, 2005), which could be helpful to cultivate emotion regulation.…”
Section: Positive Emotions and Positive Relationsmentioning
confidence: 99%
“…Research (D. M. Jr. Kivlighan, et al, 2020) provides support for the social microcosm theory where clients bring their psychosocial qualities (e.g., gratitude, psychological need satisfaction, positive affect, good relationships with others, or perceived social support) to interactions with others in a group counseling session and skills learned in the group are taken to relationships outside of the group (e.g., Yalom & Leszcz, 2005).…”
Section: The Broaden-and-build Theory and An Adaptive Spiral Effectmentioning
confidence: 99%
“…Finally, intimate behaviors can vary across groups (between-group intimate behaviors), with some groups, as a whole, having fewer and other groups having a greater number of intimate behaviors. Kivlighan et al (2021) found a moderate between-group effect, such that members in groups with more intimate behaviors, on average, compared to groups with less intimate behaviors, had a greater number of intersession intimate behaviors the following week. This finding provided support for Yalom and Leszcz (2005) theory about the social microcosm.…”
Section: My Journey As the Second Editor Of Group Dynamics: Theory Re...mentioning
confidence: 89%
“…In longitudinal group data, there are several sources of variance. For example, Kivlighan et al (2021) collected a measure of in-session intimate behaviors for every session and intersession intimate behaviors for the weeks between group sessions. A group member’s in-session intimate behaviors can vary from session-to-session (within-member intimate behavior), with some sessions having fewer and other sessions having a greater number of intimate behaviors.…”
Section: My Journey As the Second Editor Of Group Dynamics: Theory Re...mentioning
confidence: 99%
“…The prevalent feelings associated were embarrassment and discomfort, however a minority of GP patients also reported curiosity and greater sense of intimacy. These reactions evoke a wellknown theory (Yalom & Leszcz, 2005 ) that conceptualizes the group as a social space in which members play their interpersonal style in interactions with other members (Kivlighan et al ., 2021 ) and perceive the group as an environment more exposed to social judgment (Goldberg & Hoyt, 2005). These results could have interesting clinical implications suggesting that some patients felt online setting as a less safe and comfortable place and therefore less suitable for revealing their internal world.…”
Section: Discussionmentioning
confidence: 99%